Efficient promotion of charge separation and suppression of charge recombination by blending PCBM and its dimer as electron transport layer in inverted perovskite solar cells. Issue 113 (28th November 2016) - Han, Jun; Wang, Hao-Yi; Wang, Yi; Yu, Man; Yuan, Shuai; Sun, Peili; Qin, Yujun; Guo, Zhi-Xin; Zhang, Jian-Ping; Ai, Xi-Cheng
Abstract : Admixing PCBM and its dimer as electron transport material significantly improves charge carrier dynamic behavior in inverted perovskite device. Abstract : Organic–inorganic hybrid perovskite solar cells have achieved great success in recent years. Meanwhile, inverted structured device is an important branch in perovskite photovoltaics owing to its peculiar advantages of low-temperature fabrication process and non-hysteresis behavior. In this kind of device, the electron transport material, as well as the interface between perovskite and electron transport layer (ETL), plays a crucial role in photoelectric conversion process. We report that the utilization of the fullerene derivative blend, PCBM and its dumb-belled dimer, as electron transport material in inverted perovskite solar cells, which could significantly enhance the photovoltaic performances. The morphology of ETL can be regulated by changing the admixing ratio of PCBM and its dimer. Moreover, the steady-state/time-resolved fluorescence and transient photovoltage decay measurements indicate that the optimization of perovskite/ETL interface through an appropriate fullerene blend is beneficial to promote charge separation and suppress charge recombination.